Fiscal Decentralization in EU-27 Member States - Mateja Finžgar; Žan Jan Oplotnik (Naše gospodarstvo/Our economy, 2013)
The purpose of this article is to compare systems of fiscal decentralization in EU member states according to selected quantitative criteria. The results indicate that a higher number of lower levels of government usually indicate a greater share of local finance; however, this finding does not confirm the inverse link. Although the structure of expenditures is similar, the shares of funds for the implementation of in- dividual tasks differ significantly. On average, the countries allocate most funds to education, social security, healthcare, and administration, with only a quarter of the countries recording the same or higher amounts of revenues than expenditures. Most countries still cover the existing deficit through transfers from the central gover- nment, equalization schemes, or borrowed funds.